(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article discusses the translation features of the words of realities in the poem “To my brother in distance” of the outstanding Kazakh poet Magzhan Zhumabaev. The author focused on the linguistic and cultural aspect of translating the words of realities into Turkish, Russian, English in this poem, which was born at the intersection of romanticism and realism, and is one of the invaluable heritage of national literature. Conclusions are drawn on the basis of the analysis of the translation of words, which, on the one hand, reflect the national color, and on the other, require a special approach to translation. If the translation of linguistic and cultural information into other languages and the level of its reception by the reader is one of the topical issues of translation studies, the creativity and translation of Magzhan’s poetry which is the culmination apogee of Kazakh symbolism still requires research. The article uses for the first time translations into Turkish and English by Professor of the center for European, Russian and Eurasian studies Timur Kodjaoglu of the University of Michigan and a translation by A. Solovieva in Russian. Despite the fact that a huge number of scientific studies and works in translation studies have been devoted to the translation of words of national color, various strategies and methods of translation have been proposed, the question remains especially debatable among the world’s leading scholars and does not have an absolute solution to this day. Words of reality, which play an important role, reflecting the culture of the people, require a special approach to translation, thereby creating difficulties for the translator. How reflected are they in the translation? If there are changes, then what is their effect? In this article, the author tries to answer these questions.